Restoring our sanity online : a revolutionary social framework - Weinstein, Mark (Technology entrepreneur) (John Wiley & Sons, Inc., 2025)
"Big Tech is driving us, our kids, and society mad. In the nick of time, Restoring Our Sanity Online presents the bold, revolutionary framework for an epic reboot. What would social media look like if it nourished our critical thinking, mental health, privacy, civil discourse, and democracy? Is that even possible? Restoring Our Sanity Online is the entertaining, informative, and frequently jaw-dropping social reset by Mark Weinstein, contemporary tech leader, privacy expert, and one of the visionary inventors of social networking. This book is for all of us. Casual and heavy users of social media, parents, teachers, students, techies, entrepreneurs, investors, and elected officials. Restoring Our Sanity Online is the catapult to an exciting, enriching, and authentic future. Readers will embark on a captivating journey leading to an inspiring and actionable reinvention"--Provided by publisher.